Vitalizing Marital Harmony: Rethinking the Dominance of Fiqh in Cultivating Sakinah Relationships in Indonesia - Dhuha Hadiyansyah; Hunaida, Wiwin Luqna; Anasy, Zaharil (Universitas Ahmad Dahlan, 2025)
This paper aims to explain why we need to rethink the fiqh approach in fostering a sakinah marriage. To date, in various discussions about the concept of a sakinah family, both in the community in the form of religious lectures and on various social media platforms, fiqh discourse has dominated. The fiqh discourse that is the focus of this paper is the rights versus obligations of husband and wife, the age of marriage, and the ijbar rights of parents towards their daughters. In response, this study proposes an “Integrative-Mubadalah Fiqh Framework”, a paradigm that bridges the normative dimension of classical fiqh with the relational ethics of mubadalah through the epistemology of knowledge integration. This framework redefines fiqh as a dialogical and ethical discourse that promotes equality, reciprocity, and marital harmony. As a solution, the approach of knowledge integration with the principle of mubadalah or mutuality is urgent to be disseminated as a mainstream discourse in the effort to foster a sakinah marriage. Integration of knowledge in the context of marriage means synthesizing various knowledge, perspectives, data, and experiences to form a more complete picture of the issue. Therefore, one approach , fiqh, for example , cannot be enough, because other fields such as psychology, psychiatry, sociology, philosophy, and law also address the themes of marriage. The principle of mutuality allows the married couple to have an equal voice in decision-making and to share marital and family responsibilities fairly based on their respective capacities. Mutuality in marriage also increases well-being in conjugal relationships, finances, childcare, sexual satisfaction, and relationships with in-laws. Meanwhile, mainstreaming these latest concepts is vital given that marriage is the core of the social system , the failure of marriage will undermine the larger social system.